Arthroscopic partial meniscectomy for meniscal tears of the knee: a systematic review and meta-analysis - Abram, S; Hopewell, S; Monk, A; Bayliss, L; Beard, D; Price, A (BMJ Publishing Group, 2019)
Objective To assess the benefit of arthroscopic partial meniscectomy (APM) in adults with a meniscal tear and knee pain in three defined populations (taking account of the comparison intervention): (A) all patients (any type of meniscal tear with or without radiographic osteoarthritis); (B) patients with any type of meniscal tear in a non-osteoarthritic knee; and (C) patients with an unstable meniscal tear in a non-osteoarthritic knee. Design Systematic review and meta-analysis. Datasources A search of MEDLINE, Embase, CENTRAL, Scopus, Web of Science, Clinicaltrials.gov and ISRCTN was performed, unlimited by language or publication date (inception to 18 October 2018). Eligibilitycriteria Randomised controlled trials performed in adults with meniscal tears, comparing APM versus (1) non-surgical intervention; (2) pharmacological intervention; (3) surgical intervention; and (4) no intervention. Results Ten trials were identified: seven compared with non-surgery, one pharmacological and two surgical. Findings were limited by small sample size, small number of trials and cross-over of participants to APM from comparator interventions. In group A (all patients) receiving APM versus non-surgical intervention (physiotherapy), at 6–12 months, there was a small mean improvement in knee pain (standardised mean difference [SMD] 0.22 [95% CI 0.03 to 0.40]; five trials, 943 patients; I2 48%; Grading of Recommendations Assessment, Development and Evaluation [GRADE]: low), knee-specific quality of life (SMD 0.43 [95% CI 0.10 to 0.75]; three trials, 350 patients; I2 56%; GRADE: low) and knee function (SMD 0.18 [95% CI 0.04 to 0.33]; six trials, 1050 patients; I2 27%; GRADE: low). When the analysis was restricted to people without osteoarthritis (group B), there was a small to moderate improvement in knee pain (SMD 0.35 [95% CI 0.04 to 0.66]; three trials, 402 patients; I2 58%; GRADE: very low), knee-specific quality of life (SMD 0.59 [95% CI 0.11 to 1.07]; two trials, 244 patients; I2 71%; GRADE: low) and knee function (SMD 0.30 [95% CI 0.06 to 0.53]; four trials, 507 patients; I2 44%; GRADE: very low). There was no improvement in knee pain, function or quality of life in patients receiving APM compared with placebo surgery at 6–12 months in group A or B (pain: SMD 0.08 [95% CI −0.24 to 0.41]; one trial, 146 patients; GRADE: low; function: SMD −0.08 [95% CI −0.41 to 0.24]; one trial, 146 patients; GRADE: high; quality of life: SMD 0.05 [95% CI −0.27 to 0.38]; one trial; 146 patients; GRADE: high). No trials were identified for people in group C. Conclusion Performing APM in all patients with knee pain and a meniscal tear is not appropriate, and surgical treatment should not be considered the first-line intervention. There may, however, be a small-to-moderate benefit from APM compared with physiotherapy for patients without osteoarthritis. No trial has been limited to patients failing non-operative treatment or patients with an unstable meniscal tear in a non-arthritic joint; research is needed to establish the value of APM in this population.